(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
Virtual Reality (VR) is rapidly transforming education by providing immersive, interactive learning environments. This technology allows students to engage with educational content in a hands-on manner, enhancing engagement, comprehension, and retention. VR enables virtual field trips, practical simulations in fields like medicine and engineering, and enriched learning experiences across STEM subjects and history. It also holds potential for special needs education, offering personalized, adaptive environments. Despite its numerous benefits, the adoption of VR in education faces challenges, such as high costs, limited content, and the need for teacher training. As VR technology becomes more affordable and advanced, its application in education is expected to grow, bridging gaps in remote learning and making education more dynamic and accessible. This article explores the benefits, challenges, and future trends of VR in the educational landscape, highlighting its potential to revolutionize traditional learning methods.